2021
DOI: 10.1016/j.virol.2020.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of SARS-CoV-2 coinfection was not apparent on the dynamics of chronic hepatitis B infection

Abstract: In patients coinfected with SARS-CoV-2 and HBV, liver injury was common. However, the interactions between SARS-CoV-2 and HBV coinfection remained unknown. Sixty-seven COVID-19 patients from the previous cohort were enrolled and classified into 2 groups (7 with HBsAg+ and 60 with HBsAg-). The association of HBV- and SARS-CoV-2-related markers were analyzed. During the acute course of SARS-CoV-2 infection, markers of HBV replication did not extensively fluctuate during SARS-CoV-2 infection. Coinfection with HBV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 14 publications
0
14
0
5
Order By: Relevance
“…In the third step, the full text of the 372 remained articles was comprehensively studied, and we exclude the 308 studies. A total of 64 studies 3,5,18,23–79 with 61,547 total sample size were included in our study. Selection process flow chart is available in Figure 1, and Table 1 shows the studies’ characteristics.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the third step, the full text of the 372 remained articles was comprehensively studied, and we exclude the 308 studies. A total of 64 studies 3,5,18,23–79 with 61,547 total sample size were included in our study. Selection process flow chart is available in Figure 1, and Table 1 shows the studies’ characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…In the third step, the full text of the 372 remained articles was comprehensively studied, and we exclude the 308 studies. A total of 64 studies 3 , 5 , 18 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ...…”
Section: Resultsmentioning
confidence: 99%
“…The use of IFNα inhalation was reported in patients with various comorbidities and conditions, including patients with atopic dermatitis, [38] allergic rhinitis, [38] bronchiolitis, [25] chronic obstructive pulmonary disease, [84] , [162] tuberculosis, [55] cardiovascular disease, [22] hypertension, [22] , [84] , [150] , [162] diabetes, [32] , [39] hyperlipidemia, [150] obesity, [126] metabolic syndrome, [192] chronic hepatitis B infection, [76] , [153] chronic kidney disease, [22] , [70] malignancy, [163] liver transplant, [50] kidney transplant, [70] , [172] and pregnancy. [19] The use of subcutaneous injection of IFNα was reported in patients with diabetes, [42] hypertension, [42] , [44] hyperlipidemia, 42 chronic hepatitis B infection, [140] primary myelofibrosis with macrocytic anemia, [44] dementia, [44] chronic kidney disease, [44] Behcet's disease, [190] and osteoporosis.…”
Section: Comprehensive Review Of the Literature On The Safety And Efficacy Of Interferon Alpha Treatment In Covid-19 Patientsmentioning
confidence: 99%
“…During the acute course of SARS-CoV-2 infection, markers of HBV replication did not substantially fluctuate. Furthermore, the co-infection of HBV did not extend the viral shedding cycle or incubation periods of SARS-CoV-2; hence, they concluded that the effects of SARS-CoV-2 on the dynamics of chronic HBV infection were not visible and hence could not be related to the source of HBV reactivation, at least in the seven patients with chronic HBV that they studied [ 108 ]. However, the number of HBsAg-positive patients was too low to address this issue with any conviction.…”
Section: Hepatic Derangements Viral Hepatitis and Covid-19mentioning
confidence: 99%